Frequency of Sensorineural Hearing Loss in Chronic Otitis Media - Sayyed Muddasir Shah, Sahibzada Fawad Khan, Mubashar Ullah Jan, Haider Zaman (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To identify the frequency of sensorineural hearing loss in chronic otitis media. Study Design: Cross-sectional study. Place and Duration of Study: Department of ENT, Bacha Khan Medical College, Mardan Medical Complex Mardan from 1st October 2019 to 30th September 2021. Methodology: One hundred patients with chronic suppurative otitis media clinical symptoms and diagnosis were included in the study. The age of the patients was between 11-50 years. A mean of 0.05 an average result of three recorded frequencies on an audiogram was calculated. With an increase in chronic suppurative otitis media duration the number of sensorineural hearing loss patients was determined. Results: The mean age was 36.3±6.6 years with 54% males and 46% females. The frequency of sensorineural hearing loss was reported as 51 (51%) of the otitis media disease patients were suffering from sensorineural hearing loss condition while the similar condition was not seen in the 49% of the chronic suppurative otitis media patients. Conclusion: A high frequency of sensorineural hearing loss was recorded in the chronic suppurative otitis media patients.